Fractal Dimensions in Evaluation of Heart Function Parameters during Physical Investigations (Baltic Journal of Sport and Health Sciences, 2018)
In last two decades the theory of complex systems made big steps in its development. The new methods for integralsituations’ evaluations were created. Beginning from F. Hausdorff in 1919, the set of fractal dimensions was proposedto evaluate systems’ complexity. Now F. Hausdorff’s dimension, A. Kolmogorov’s integral correlation dimension,information dimension, correlation dimension and many others are widely used. They are used in physics, medicine,biology, astronomy and all other sciences. The question still exists which, when to use and what additional informationit will provide. The aim of this work was to explore the behavior of a few well known fractal dimensions during physicalinvestigations of healthy persons, sportsmen and ischemic heart diseased patients with the aim to evaluate the heartfunction. The studied fractal dimensions can be used for the evaluation of a sportsman’s functional state. Theendurance-trained sportsman has the highest values of fractal dimensions. Information dimension detects newunstudied information in sport and clinical medicine. It separates out the investigated persons according to gender,disease and physical activity. But information dimension does not depend on age in the investigated groups ofasymptomatic persons (men and women).Keywords: cardiovascular system, functional state, complexity, fractal dimensions.